Nursing professionals’ attitudes, strategies, and care practices towards death: a systematic review of qualitative studies. - Puente-Fernández, Daniel; Lozano-Romero, María Mercedes; Montoya-Juárez, Rafael; Martí-García, Celia; Campos-Calderón, Concepción; Hueso-Montoro, César (Wiley, 2020)
Purpose: To explore the attitude of nursing professionals towards death. Design: Systematic qualitative review methods were used. Methods: A search was conducted in the PubMed, Web of Science, CINAHL, and CUIDEN databases. This study included 17 articles. Findings: Thirteen categories emerged, which were grouped into three themes: meanings and feelings during the dying process; coping strategies in the face of death; and the importance of training, experience, and providing a dignified death. In the different accounts of the participants, it was found that death had a large negative emotional impact on them, that the participants complained about the lack of previous training in the care of dying patients, and that avoiding these complex situations was one of the strategies most commonly used by professionals to face the death of a patient. Conclusions: The lack of training in the basic care of terminally ill patients, as well as today’s preconceived negative idea about death, both cause health professionals to experience situations of great stress and frustration. This results, on many occasions, in resorting to avoiding these situations, thus preventing dying with dignity. Clinical relevance: In this paper, we explore the consequences of this process for nursing professionals, common coping strategies, and possible areas for improvement, such as the need for the training of nursing professionals in the care of terminally ill patients and their families.
Keywords: Cuidados terminales; Enfermeras; Personal sanitario; Muerte; Death; Attitudes towards death; Healthcare professionals; Nurses